2010
DOI: 10.1007/s11103-010-9652-1
|View full text |Cite
|
Sign up to set email alerts
|

Sumoylation of Arabidopsis heat shock factor A2 (HsfA2) modifies its activity during acquired thermotholerance

Abstract: Post-translational modification of target proteins by the small ubiquitin-like modifier protein (SUMO) regulate many cellular processes. In this work we show SUMOylation of the heat shock transcription factor, AtHsfA2, in connection with the plant's response to heat stress and acquired thermotolerance. Using the Yeast two hybrid and the bimolecular fluorescence complementation system, we have found that AtSUMO1 physically interacts with AtHsfA2. Further investigation allowed us to determine that Lys 315 of AtH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 75 publications
(100 reference statements)
1
61
0
Order By: Relevance
“…Notable examples were the RNA splicing/degrading/helicase proteins RSP35, RSP41, PRH75, U2AF65A, SDN3, STA1, and NUC-L1; the RNA binding proteins LA1 and CCR2; and the RNAdependent DNA methylation-related protein IDN2. Non-RNArelated factors experiencing strong increases in SUMOylation state (Ͼ7-fold) after heat stress included the heat shock transcription factor HSF2A, a previously identified SUMO target known to be important for establishing long-term acquired thermotolerance (27,41,55). Also among the Tier 1 targets was an Arabidopsis ortholog of the mammalian SIM-containing DNA gyrase MORC involved in heterochromatin condensation and transcriptional repression (56,57), the POLD3 DNA polymerase core subunit, and the histone-binding protein NRP1.…”
Section: Development Of a Quantitative Proteomic Strategy To Monitor mentioning
confidence: 99%
See 1 more Smart Citation
“…Notable examples were the RNA splicing/degrading/helicase proteins RSP35, RSP41, PRH75, U2AF65A, SDN3, STA1, and NUC-L1; the RNA binding proteins LA1 and CCR2; and the RNAdependent DNA methylation-related protein IDN2. Non-RNArelated factors experiencing strong increases in SUMOylation state (Ͼ7-fold) after heat stress included the heat shock transcription factor HSF2A, a previously identified SUMO target known to be important for establishing long-term acquired thermotolerance (27,41,55). Also among the Tier 1 targets was an Arabidopsis ortholog of the mammalian SIM-containing DNA gyrase MORC involved in heterochromatin condensation and transcriptional repression (56,57), the POLD3 DNA polymerase core subunit, and the histone-binding protein NRP1.…”
Section: Development Of a Quantitative Proteomic Strategy To Monitor mentioning
confidence: 99%
“…Prior studies with related HSFs in mammalian cells showed that their heat-shock-stimulated SUMOylation affects binding to their cognate promoter elements, although the direction of the response remains in question (71)(72)(73). Given the role of HSFA2 in the establishment of acquired thermotolerance, it is tempting to speculate that its SUMOylation not only is involved in basal stress tolerance (7,28), but also serves as a guard against future insults (27).…”
Section: Development Of a Quantitative Proteomic Strategy To Monitor mentioning
confidence: 99%
“…In Arabidopsis, HSFA2 is targeted for SUMOylation during extended exposure to heat stress and recovery (Cohen-Peer et al, 2010). In this case, SUMOylation negatively regulates the activity of this transcription factor.…”
mentioning
confidence: 99%
“…AtHsfA2 also plays an important role in linking heat shock with oxidative stress signals . A recent study (Cohen-Peer et al, 2010) has demonstrated AtSUMO1 of AtHsfA2 to be involved with the plant's regulatory response to heat stress and acquired thermotolerance. Post-translational modification of target proteins by SUMO proteins (see cold section for background) regulates many cellular processes, and adds a further layer to this complex network In a recent study to identify potential regulatory components involved in thermotolerance, a reverse genetics approach was used by screening Arabidopsis T-DNA insertion mutants for lines displaying phenotypic decreased thermotolerance.…”
Section: Heat Stressmentioning
confidence: 99%